2020
DOI: 10.1002/yea.3513
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic potential of Saccharomyces cerevisiae and Kluyveromyces marxianus isolated from West African spontaneously fermented cereal and milk products

Abstract: The yeast species Saccharomyces cerevisiae and Kluyveromyces marxianus are associated with fermentation of West African indigenous foods. The aim of this study was to characterize potential probiotic properties of S. cerevisiae and K. marxianus isolates from the West African milk products lait caillé and nunu and a cerealbased product mawè. The strains (14 in total) were identified by 26S rRNA gene sequencing and characterized for survival at gastrointestinal stress (bile salts and low pH) and adhesion to Caco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…It was reported that the pasta can keep probiotic traits after six months of storage due the viability of the organism. For another microorganism group, yeast species were also studied in this manner (Motey et al , 2020). The probiotic potential of Saccharomyces cerevisiae and Kluyveromyces marxianus isolated from West African spontaneously fermented cereals and milk products was investigated by several probiotic criteria tests (Motey et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the pasta can keep probiotic traits after six months of storage due the viability of the organism. For another microorganism group, yeast species were also studied in this manner (Motey et al , 2020). The probiotic potential of Saccharomyces cerevisiae and Kluyveromyces marxianus isolated from West African spontaneously fermented cereals and milk products was investigated by several probiotic criteria tests (Motey et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For another microorganism group, yeast species were also studied in this manner (Motey et al , 2020). The probiotic potential of Saccharomyces cerevisiae and Kluyveromyces marxianus isolated from West African spontaneously fermented cereals and milk products was investigated by several probiotic criteria tests (Motey et al , 2020). Selected strains were suggested for further development as starter cultures in West African fermented products.…”
Section: Resultsmentioning
confidence: 99%
“…Pichia kudriavzevii was reported in another spontaneously fermented pearl millet product, fura, in West Africa (Pedersen et al, 2012), ogi (Omemu et al, 2007), and gowé (Greppi et al, 2013). K. marxianus is one of the promising yeast species isolated from fermented foods with beneficial characteristics and has been associated with spontaneous fermentation in West Africa (Karim et al, 2020;Motey et al, 2020). All the yeasts profiled at the different time points may contribute to production of aroma compounds from different carbon sources, mycotoxin degradation, increase in shelf life, safety, and nutritional value of Hausa koko (Forti et al, 2018;Johansen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Wickerhamomyces anomalus , S. cerevisiae and Pichia kudriavzevii isolated from Egyptian traditional cheese, have shown potential probiotic properties such as high tolerance to bile salts, lowest eradication from intestinal mucosa (Helmy et al, 2019). Probiotic potentials of S. cerevisiae and K. marxianus , isolated from some West African naturally fermented milk products such as nunu and lait caillé , have been reported, which included high or moderate tolerance to bile salts, adhesion to Caco‐2 cells and potentiality to improve intestinal barrier functions (Motey et al, 2020). Candida guilliermondii , isolated from Indonesian traditional fermented buffalo‐milk product called dangke , was able to resist pH 4, bile salts (Table 1) and had the ability to aggregate Salmonella spp., one of the important probiotic attributes of yeast (Utama et al, 2019).…”
Section: Yeasts With Probiotic Properties In Fermented Foodsmentioning
confidence: 99%